Aggregation Pheromone of Coconut Rhinoceros Beetle, Oryctes rhinoceros (L.) (Coleoptera: Scarabaeidae) - Hallett, Rebecca H. (1995)
Male coconut rhinoceros beetles,Oryctes rhinoceros (L.), produce three sex-specific compounds, ethyl 4-methyloctanoate, ethyl 4-methylheptanoate, and 4-methyloctanoic acid, the first of which is an aggregation pheromone. Synthesis of these compounds involving conjugate addition of organocuprates to ethyl acrylate is reported. In field trapping experiments, (4S)-ethyl 4-methyloctanoate and the racemic mixture were equally attractive and 10 times more effective in attracting beetles than ethyl chrysanthemumate, a previously recommended attractant. Ethyl 4-methylheptanoate was as attractive as ethyl chrysanthemumate and more attractive than 4-methyloctanoic acid, but further studies are required before it can be classed as an aggregation pheromone. Compared to ethyl 4-methyloctanoate alone, combinations of the three male-produced compounds did not increase attraction, whereas addition of freshly rotting oil palm fruit bunches to pheromone-baited traps significantly enhanced attraction. With increasing dose, captures of O. rhinoceros increased, but doses of 6, 9, and 18 mg/day were competitive with 30 mg/day lures. Newly designed vane traps were more effective in capturing beetles than were barrier or pitfall traps. Results of this study indicate that there is potential for using ethyl 4-methyloctanoate in operational programs to control O. rhinoceros in oil palm plantations.